2006
DOI: 10.1007/s10620-006-3173-4
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Induced Proliferation in Cultured Hepatocytes Involves Cyclin D1, P21CIP1 and P27KIP1

Abstract: The purpose of this study was to establish if estrogen-induced hepatocyte proliferation in vitro involves the cell cycle regulators cyclin D1, p21(Cip1), and p27(Kip1). Male rat hepatocytes were cultured in presence of 17-beta-estradiol (E2) +/- ICI-182780, a pure estrogen antagonist, and [3H]-thymidine, as required. DNA synthesis as well as p21(Cip1), p27(Kip1), and cyclin D1mRNA and protein levels were evaluated at different times (12, 24, 36, and 48 hours) of incubation. E2-increased DNA synthesis was corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition to regulating sex steroid hormones, hepatocytes express ER␣ and AR and respond to estrogens and androgens (21). For example, E2 has both proliferative and metabolic effects on hepatocytes in culture and in vivo (4,19,22). E2 has been shown to promote proliferation of male primary hepatocytes and hepatocellular carcinoma (HCC) cells in culture (4,19).…”
Section: Take Down Policymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to regulating sex steroid hormones, hepatocytes express ER␣ and AR and respond to estrogens and androgens (21). For example, E2 has both proliferative and metabolic effects on hepatocytes in culture and in vivo (4,19,22). E2 has been shown to promote proliferation of male primary hepatocytes and hepatocellular carcinoma (HCC) cells in culture (4,19).…”
Section: Take Down Policymentioning
confidence: 99%
“…For example, E2 has both proliferative and metabolic effects on hepatocytes in culture and in vivo (4,19,22). E2 has been shown to promote proliferation of male primary hepatocytes and hepatocellular carcinoma (HCC) cells in culture (4,19). Studies have also suggested that increased estrogen levels may correlate with an increased risk of HCC in men and postmenopausal women (8,40).…”
Section: Take Down Policymentioning
confidence: 99%
“…Phosphorylation on S118 of ERα is one such modification that can lead to tamoxifen resistance [51]. Cellular cycling influences the phosphorylation status of ERα in a manner that is dependent upon mitogen stimulation [25, 68]. In particular, phosphorylation on S118 is regulated by activated ERK1/2 [33, 34, 51].…”
Section: Discussionmentioning
confidence: 99%
“…15 It has been previously shown that estrogen can act as a strong mitogen for hepatocytes and helps promote regeneration by increasing levels of cyclin D1 messenger RNA (mRNA) levels in hepatocytes. 16 Ovariectomized female rats given estrogen pellets showed a greater liver regeneration after portal branch ligation as compared to untreated ovariectomized female rats. 17 Similarly, the treatment of tamoxifen, an estrogen antagonist, to rats after partial hepatectomy (PHX) shows a decrease in hepatocyte proliferation.…”
Section: Introductionmentioning
confidence: 92%